PERILAKU MASYARAKAT DALAM MENERAPKAN PROTOKOL PENCEGAHAN COVID-19 - lisavina juwita; ninda adriana; sherly amelia (HUMAN CARE JOURNAL, 2021)
The development of the Covid-19 outbreak is increasingly worrying where every day there is an increase in cases globally. In West Sumatra the total number of cases was 65,703 and the City of Bukittinggi the number of cases was 2471 cases. This study aims to determine the behavior of the community in implementing the Covid-19 prevention protocol in the community. This type of research is a descriptive study in June 2021 with a population of all adults in Kelurahan G, Bukittinggi City. Sampling using purposive sampling technique with a sample size of 96 respondents. Collecting data using a questionnaire. Data analysis includes editing, coding and data entry. The results showed that the behavior of implementing the Covid-19 prevention protocol was not good, namely 47% of respondents rarely kept their distance when in crowds, 57% of respondents rarely washed their hands with soap or hand sanitizer after handling objects in public places and 40% of respondents never wore masks that were three layers when outdoors. It is hoped that the community will always improve the Covid-19 prevention protocol in order to avoid exposure to the community from Covid-19